The effect of pharmaceutical co-payment increase on the use of social assistance—A natural experiment study - Hanna Rättö; Katri Aaltonen (PLOS, 2022)
Health care out-of-pocket payments can create barriers to access or lead to financial distress.
Out-of-pocket expenditure is often driven by outpatient pharmaceuticals. In this
nationwide register study, we study the causal relationship between an increase in patients’
pharmaceutical expenses and financial difficulties by exploiting a natural experiment design
arising from a 2017 reform, which introduced higher co-payments for type 2 diabetes medicines
in Finland. With difference-in-differences estimation, we analyze whether the reform
increased the use of social assistance, a last-resort financial aid. We found that after the
reform the share of social assistance recipients increased more among type 2 diabetes
patients than among a patient group not affected by the co-payment increase, suggesting
the reform increased the use of social assistance among those subject to it. The results indicate
that increases in patients’ pharmaceutical expenses can lead to serious financial difficulties
even in countries with a comprehensive social security system.